Effects of Foliar Nutrition on Onion Seed Storage under Controlled Atmosphere - Shehata, S. A.; Hashem, M. Y.; Mahmoud, G. I.; Abd El-Gawad, K. F.; El-Ramady, H. R.; Alshaal, T. A.; Domokos-Szabolcsy, É.; Elhawat, N.; Prokisch, J.; Fári, M. (International Journal of Horticultural Science, 2013)
Storage of fresh fruits and vegetables prolongs their usefulness. The principal goal of storage is to preserve the commodity in its most useable form for the consumer. The extension of storage life and the improvement of quality of fresh fruits and vegetables can be supplied by harvesting at proper maturity, control of post-harvest diseases, chemical treatments, refrigeration, controlled and modified atmospheres. Two successive winter seasons of 2008/2009 and 2009/2010 were conducted under sandy soil conditions to study the effect of spraying with 12 commercial compounds on onion seeds and storage under controlled atmosphere. The germination percentages were 85.50, 86.85, 83.75 and 82.15 for CA1, CA2, CA3 and CA4, respectively. Water content of onion seeds was significantly increased with decreasing storage temperature in all controlled atmospheres. Water content values were 4.48, 4.40, 4.55 and 4.54 for CA1, CA2, CA3 and CA4, respectively. There were significant decreases in water content with increasing exposure periods. The lowest water content was recordednfor the exposure periods of 120 and 240 days. Catalase and peroxidase activities were decreased with the decreasing of storage temperature, whereas malondialdehyde content was increased. The exposure for 120 days recorded the highest catalase activity. The highest value of peroxidase (11.72) was recorded for CA2. Peroxidase activity increased as exposure period increased until 120 days and then decreased. Cold storage temperature (5°C) showed the highest malondialdehyde content followed by room temperature. The CA2 showed the lowest malondialdehyde content compared with other controlled atmospheres. The exposure period of 120 days had the lowest malondialdehyde content.